Strategy to enhance efficacy of doxorubicin in solid tumor cells by methyl-β-cyclodextrin: Involvement of p53 and Fas receptor ligand complex - Mohammad, Naoshad (Sci Rep, 2015)
Doxorubicin (DOX) is one of the preferred drugs for treating breast and liver cancers. However, its clinical application is limited due to severe side effects and the accompanying drug resistance. In this context, we investigated the effect on therapeutic efficacy of DOX by cholesterol depleting agent methyl-β-cyclodextrin (MCD), and explored the involvement of p53. MCD sensitizes MCF-7 and Hepa1–6 cells to DOX, Combination of MCD and marginal dose of DOX reduces the cell viability, and promoted apoptosis through induction of pro-apoptotic protein, Bax, activation of caspase-8 and caspase-7, down regulation of anti-apoptotic protein Bcl-2 and finally promoting PARP cleavage. Mechanistically, sensitization to DOX by MCD was due to the induction of FasR/FasL pathway through p53 activation. Furthermore, inhibition of p53 by pharmacological inhibitor pifithrin-α (PFT-α) or its specific siRNA attenuated p53 function and down-regulated FasR/FasL, thereby preventing cell death. Animal experiments were performed using C57BL/6J mouse isografted with Hepa1–6 cells. Tumor growth was retarded and survival increased in mice administered MCD together with DOX to as compared to either agent alone. Collectively, these results suggest that MCD enhances the sensitivity to DOX for which wild type p53 is an important determinant.